Modification of Sorghum bicolor (L) Moench Starch: Review of HMT (Heat Moisture Treatment), Autoclaving Cooling, and Annealing Methods - Riski Ayu Anggreini; Nurul Azizah Choiriyah; Armita Athennia (Universitas PGRI Semarang, 2021)
The use of sorghum in Indonesia is still not optimal even though it ranks as the third most cultivated cereal category. Its carbohydrate content, especially starch, is high enough to provide a large enough potential for sorghum to be developed and applied to food products. Starch is used for improving the final product characteristics such as texture, flavor, and functionality. Several physical modification methods have been investigated to improve the final product characteristics of sorghum. The physical modification method of starch has advantages over chemical or enzyme methods, it is easy to apply, safe, and faster. This review aims to summarize the physical modification of sorghum starch using heat moisture treatment, autoclaving cooling, and annealing methods for the characteristics or functionality produced. Heat moisture treatment (HMT) and Annealing have affected the swelling power and solubility significantly while Autoclaving Cooling increases the amylose content and significantly reduces the digestibility of the starch.